Generalised class of starlike functions of Koebe type with complex order - Mohd Nazran Mohammed Pauzi,; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this paper, we investigate some results on subordination, superordination, best dominant result and the sandwich theorem of the new class Hb    , ,  of analytic functions with Koebe type. Further, by making use of Jack’s Lemma as well as several differential and other inequalities, sufficient condition for starlikeness of the class Hb    , ,  of n-fold symmetric analytic functions of Koebe type is derived. Relevant connections of the results presented here with those given in earlier works are also indicated.